Edukacja uczniów z niepełnosprawnością sprzężoną w Republice Czeskiej - KASPRZAK, TOMASZ (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Tomasz Kasprzak, Education of pupils with multiple disabilities in the Czech Republic, Interdisciplinary Contexts of Special Pedagogy, No. 22, Poznań 2018. Pp. 289–303. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.16 Currently, recognition of the right of all people to education is considered completely natural. Since the mid-1990s, in the Czech Republic, the issue of educating people with multiple disabilities has been increasingly addressed. The main purpose of this study is to characterise the approach to education of persons with multiple disabilities in the Czech Republic. The article contains interpretations of the concept of multiple disabilities, both in the Czech literature and in international literature, with particular emphasis on the Czech approach.